Effects of Parboiling on Chemical Properties, Phenolic Content and Antioxidant Capacity in Colored Landrace Rice - Wanwipa Pinta; Chorkaew Aninbon; Phissanu Kaewtaphan; Kannika Kunyanee (Foods, 2024)
Parboiling influences chemical compositions in rice grains. The objectives of this study were to evaluate the change in chemical content, total phenolic content and antioxidant capacity of landrace rice genotypes under parboiling conditions and to identify the genotypes suitable for production of parboiled rice. Landrace rice varieties used in this study consisted of Glam Feang, Glam Tonkeaw, Kawgum, Glam Luem Phua, Medmakham, Deang Sakonnakhon, Sang Yod, Kawniewd-eang, Mali Deang, KDML105 and RD6. Parboiling reduced fiber content, total phenolic content and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical-scavenging activity in rice grains. Fiber contents were 1.46% in brown rice (unpolished rice) and 1.40% in parboiled rice (24 h of soaking and 48 h of incubation). Total phenolic contents were 205.67 mg/100 g seed in brown rice and 35.34 mg/100 g seed in parboiled rice. Antioxidant capacity (DPPH) reduced from 68.45% in brown rice to 26.23% in parboiled rice. Ash content and protein content were not significantly affected by the parboiling process. Medmakham cv. had the highest total phenolic content and antioxidant capacity in brown rice and parboiled rice. Gum Leamphea cv. and Medmakham cv. were the best genotypes for ash content, protein content, total phenolic content and antioxidant capacity (DPPH) in brown rice and parboiled rice. Glam Feang cv. had the highest protein contents in brown rice and parboiled rice although it had low total phenolic content and antioxidant capacity. Cluster analysis further showed variation among genotypes, revealing distinct groupings in brown rice and parboiled rice based on chemical properties, phenolic content and antioxidant capacity. This research significantly contributes to a better understanding on how parboiling affects rice compositions and nutritional values. It emphasizes the importance of nuanced comprehension of how different rice varieties respond to parboiling, aiding informed decisions in rice processing and selection to meet specific nutritional needs.
Keywords: Food composition and properties; GABA and Rice Research; Phytochemicals and Antioxidant Activities